2022
DOI: 10.21203/rs.3.rs-1619662/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomic Profiling of Equine Cord Blood Mesenchymal Stromal Cells in Both Early and Late Stages of Culture

Abstract: Introduction: Equine Mesenchymal Stromal Cells (MSC) hold great potential as a future form of cellular therapy. Fetal Bovine Serum (FBS) is used as a supplement MSC culture, but challenges with its use have initiated a desire to create a defined media to expand these cells. MSCs have shown great variability in species, tissue source and passage number. Due to this, to effectively create a replacement for FBS we must better understand how it meets the metabolic needs for each type of MSC. Objectives: The goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another group of researchers found no difference in proliferation of equine BM-MSC and canine AD-MSC grown in StemPro SFM when compared to FBS ( 18 ). Work done in our lab found that using StemPro SFM in equine CB-MSC culture resulted in slower proliferation compared to FBS ( 96 ). These differences could be attributed to tissue source variation.…”
Section: Fbs In Msc Culturementioning
confidence: 99%
“…Another group of researchers found no difference in proliferation of equine BM-MSC and canine AD-MSC grown in StemPro SFM when compared to FBS ( 18 ). Work done in our lab found that using StemPro SFM in equine CB-MSC culture resulted in slower proliferation compared to FBS ( 96 ). These differences could be attributed to tissue source variation.…”
Section: Fbs In Msc Culturementioning
confidence: 99%